Safety and efficacy of PD-1 inhibitor (sintilimab) combined with transarterial chemoembolization as the initial treatment in patients with intermediate-stage hepatocellular carcinoma beyond up-to-seven criteria - Lei Yu; Lan Zhang; Xin Xu; Zheng Wang; Jian Zhou; Jia Fan; Wentao Wang; Zhenggang Ren; Lixing Li; Peiran Huang (Journal for ImmunoTherapy of Cancer)
Background Numerous studies have demonstrated limited survival benefits of transarterial chemoembolization (TACE) alone in the treatment of intermediate-stage hepatocellular carcinoma (HCC) beyond up-to-seven criteria. The advent of immunotherapy, particularly immune checkpoint inhibitors (ICIs), has opened new avenues for HCC treatment. However, TACE combined with ICIs has not been investigated for patients with intermediate-stage HCC beyond the up-to-seven criteria. The study aims to evaluate the efficacy and safety of this treatment strategy for such patients.Methods In this single-arm, prospective, phase II study, we enrolled eligible patients with HCC who were treated with TACE plus programmed cell death protein 1 (PD-1) inhibitors (sintilimab) from April 2021 to February 2023. The study’s primary objectives were to assess progression-free survival (PFS) and safety. Secondary objectives included measuring the objective response rate (ORR) and disease control rate (DCR) as per both Response Evaluation Criteria in Solid Tumors (RECIST) V.1.1 and modified RECIST (mRECIST) criteria, as well as overall survival (OS). Additionally, we conducted correlation analyses to identify predictors influencing the efficacy of tumor treatment.Result 20 patients participated in this study, with a median follow-up duration of 22.0 months. Median PFS was 8.4 months (95% CI: 4.7 to 19.7) according to both RECIST V.1.1 and mRECIST. The ORR was 30.0% (95% CI: 14.6% to 51.9%) per RECIST 1.1% and 60% (95% CI: 38.7% to 78.1%) per mRECIST. DCR was 95.0% (95% CI: 76.4% to 99.1%) according to both RECIST V.1.1 and mRECIST. Median OS was not yet reached. Notably, 20% (4/20) of patients underwent successful conversion to curative surgical resection. Treatment-related adverse events (TRAEs) mainly included elevated aspartate aminotransferase levels (19/20, 95.0%), elevated alanine aminotransferase levels (18/20, 90.0%), hypothyroidism (18/20, 90.0%), and reduced appetite (10/20, 50.0%). Among all participants, only one experienced grade 3 TRAE (myocarditis). We employed the Elastic Net regression model to analyze radiomic features from tumor and peritumoral areas to predict the efficacy of this treatment strategy.Conclusion TACE plus PD-1 inhibitors demonstrated promising efficacy and an acceptable safety profile, suggesting it as a potential treatment option for patients with intermediate-stage HCC beyond up-to-seven criteria. Furthermore, our study indicates that specific image-based features may serve as predictors for patients likely to benefit from this treatment approach.Trial registration number NCT04842565.